2003
DOI: 10.1002/jcb.10342
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic 25‐hydroxyvitamin D‐1α‐hydroxylase and its implication in prostate cancer

Abstract: Evidence suggests that vitamin D may have a protective role for prostate cancer. 1alpha,25-Dihydroxyvitamin D [1alpha,25(OH)(2)D] inhibits growth and induces differentiation of prostate cells. 25-Hydroxyvitamin D-1alpha-hydroxylase [1alpha-OHase], the enzyme that is responsible for the synthesis of 1alpha,25(OH)(2)D, is expressed in cultured prostate cells. We observed a marked decrease in 1alpha-OHase activity in prostate cancer cells, suggesting some defect of the 1alpha-OHase in these cells. To investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(75 citation statements)
references
References 23 publications
5
70
0
Order By: Relevance
“…Interestingly, epithelial prostate cells express 1␣-hydroxylase, which is required for 1,25-dihydroxyvitamin D 3 synthesis (51). The extrarenal synthesis of 1,25-dihydroxyvitamin D 3 in the prostate could have a local growth-regulating physiological role, as suggested by the marked decrease of 1␣-hydroxylase activity in prostate cancer cell lines (52), and possibly also an anti-inflammatory one. Although the prostate has been long recognized as a target organ of VDR agonists (49), its capacity to respond to these agents has thus far been probed only for the treatment of prostate cancer (53) and BPH (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, epithelial prostate cells express 1␣-hydroxylase, which is required for 1,25-dihydroxyvitamin D 3 synthesis (51). The extrarenal synthesis of 1,25-dihydroxyvitamin D 3 in the prostate could have a local growth-regulating physiological role, as suggested by the marked decrease of 1␣-hydroxylase activity in prostate cancer cell lines (52), and possibly also an anti-inflammatory one. Although the prostate has been long recognized as a target organ of VDR agonists (49), its capacity to respond to these agents has thus far been probed only for the treatment of prostate cancer (53) and BPH (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…The initial demonstration that 1,25-(OH) 2 D 3 is an antiproliferative, prodifferentiating agent for certain cell types in vivo and many cell lines in vitro ( 152 ), coupled with the fact that cancer cell studies have showed decreased CYP27B1 and increased CYP24A1 expression in prostatic, colonic, and breast cell lines as they progress toward a more tumorigenic phenotype ( 97,(153)(154)(155)(156), has caused Of these, only IIH has unknown etiology and, until recently, had no gene locus assigned to it ( 164,165 ). In 2011, Schlingmann et al ( 166 ) demonstrated that loss-offunction mutations of CYP24A1 were an underlying cause of IIH in nine families of German, Turkish, and Russian origin.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Thus, over-expression of 24-hydroxylase may further abrogate growth control mediated by 1a,25(OH) 2 D 3 , via target cell inactivation of the hormone. It has therefore been proposed that breast cancer is associated with low circulating concentrations of 25OH-D, arising as a result of reduced exposure to sunlight, altered dietary patterns and impaired generation of 1a,25(OH) 2 D 3 within breast tissue (51,(117)(118)(119)(120)(121) .…”
Section: Epidemiological Evidencementioning
confidence: 99%